Customer perspectives on district heating price models - Sernhed, Kerstin; Gåverud, Henrik; Sandgren, Annamaria (International Journal of Sustainable Energy Planning and Management, 2017)
In Sweden there has been a move towards more cost reflective price models for district heating in order to reduce economic risks that comes with variable heat demand and high shares of fixed assets. The keywords in the new price models are higher shares of fixed cost, seasonal energy prices and charging for capacity. Also components that are meant to serve as incentives to affect behaviour are introduced, for example peak load components and flow components. In this study customer responses to these more complex price models have been investigated through focus group interviews and through interviews with companies that have changed their price models. The results show that several important customer requirements are suffering with the new price models. The most important ones are when energy savings do not provide financial savings, when costs are hard to predict and are perceived to be out of control.